A novel high entropy perovskite oxide with co-substitution in A and B sites (Ca1/3Sr1/3Ba1/3)(Y1/4Zr1/2Nb1/4)O3 design, synthesis and structural characterization. Issue 5 (1st March 2023) - Yang, Yuchen; Li, Haitao; Duan, Baohua; Feng, Qisheng; Li, Cuixia; Lu, Xionggang; Chen, Guangyao; Li, Chonghe
Abstract: A novel high-entropy perovskite oxide (HEPO) (Ca1/3 Sr1/3 Ba1/3 )(Y1/4 Zr1/2 Nb1/4 )O3 (CSBYZN) was designed and synthesized by solid-state reaction method by the use of CaCO3, SrCO3, BaCO3, Y2 O3, ZrO2 and Nb2 O5 . Due to the substitution of the cations at both the A and B sites, the configuration entropy of CSBYZN was higher than that of other HEPOs with only one Wyckoff site (A or B site) substituted with 5 elements. The crystal structure of CSBYZN was identified as a cubic structure of the Pm-3m space group by Rietveld refinement. The measured lattice constant a = 4.1242 Å is similar to the value obtained by using the empirical formula (acal  = 4.1229 Å). It was proved that the lattice constant of HEPOs can be predicted by the empirical formula. This study provides a new thought for the design of novel HEPOs.